Reducing Maternal Mortality Rate Through Utilization of Agricultural Products and Antenatal Care with Agronursing Perspective: Upaya Penurunan Maternal Mortality Rate Melalui Pemanfaatan Hasil Pertanian dan Antenatal Care di Wilayah Agronursing - Puspitasari, R.A. Helda; Handayani, Dwining; Kusuma, Erik; Dewi Nastiti, Ayu (KHD Production, 2023)
In Indonesia, the number of deliveries assisted by health personnel is still relatively low. Pregnancy checks (Antenatal Care = ANC) can motivate pregnant women to give birth to health workers. This study aims to determine the role of ANC in selecting birth attendants. This cross-sectional study used secondary data from the KKG Project Benefit Evaluation Survey (Family Health and Nutrition)—efforts to Reduce Maternal Mortality Rate Through Utilization of Agricultural Products and Antenatal Care in Agronursing Areas. Maternal Mortality Rate (MMR) is the death of a woman during pregnancy or 42 days after giving birth. Indonesia is a country with a significant increase in the number of maternal mortalities of 359/100,000. This achievement still needs to catch up to the 2024 Millennium Development Goals (MDGs) target, which is 183/100,000 KH, so this has made Indonesia experience a crisis in maternal health services. The low readiness of the mother to fulfill nutritional quality and conduct antenatal care can be a big problem in the birth process. Therefore, it is important to carry out socialization to reduce the maternal mortality rate by utilizing agricultural products to improve maternal nutrition through antenatal care. The purpose of doing community service for pregnant women is to reduce the Maternal Mortality Rate in Indonesia. Community empowerment is carried out by conducting lectures between researchers and participants.